Cutaneous Pyogranulomas Associated with Nocardia jiangxiensis in a Cat from the Eastern Caribbean - Silkworth, Adam (Trop Med Infect Dis, 2019)
Nocardia spp. are worldwide, ubiquitous zoonotic bacteria that have the ability to infect humans as well as domestic animals. Herein, we present a case of a five-year-old female spayed domestic shorthair cat (from the island of Nevis) with a history of a traumatic skin wound on the ventral abdomen approximately two years prior to presenting to the Ross University Veterinary Clinic. The cat presented with severe dermatitis and cellulitis on the ventral caudal abdomen, with multiple draining tracts and sinuses exuding purulent material. Initial bacterial culture yielded Corynebacterum spp. The patient was treated symptomatically with antibiotics for 8 weeks. The cat re-presented 8 weeks after the initial visit with worsening of the abdominal lesions. Surgical intervention occurred at that time, and histopathology and tissue cultures confirmed the presence of Nocardia spp.-induced pyogranulomatous panniculitis, dermatitis, and cellulitis. Pre-operatively, the patient was found to be feline immunodeficiency virus (FIV)-positive. The patient was administered trimethoprim/sulfamethoxazole (TMS) after antimicrobial sensitivity testing. PCR amplification and 16S rRNA gene sequencing confirmed Nocardia jiangxiensis as the causative agent. To our knowledge, N. jiangxiensis has not been previously associated with disease. This case report aims to highlight the importance of a much-needed One Health approach using advancements in technology to better understand the zoonotic potential of Nocardia spp. worldwide.